tRF-1:28-Val-CAC-2 promotes the development of nasopharyngeal cancer by targeting EPHB2 - Li, Hui; Wang, Xiaomin; Sun, Anchi; Liu, Weiwei; Lv, Rongrong; Zhang, Mingjie; Xing, Zhiwei; Ma, Shiyin; Liu, Yehai; Zhang, Kai (Frontiers in Oncology, 2025)
IntroductionNasopharyngeal carcinoma (NPC) is highly aggressive, with a particularly high incidence in South China. is an aggressive cancer that affects particularly high numbers of patients in southern China and Southeast Asia. The cure rate of previous treatments is decreasing year by year, underscoring the need to devise new approaches to treating affected patients. This study was developed to examine the tRF-1:28-Val-CAC-2 expression in NPC and to elucidate its effects on proliferative, migratory, and apoptotic dynamics in NPC cells.MethodsRT- qPCR was used to quantify tRF-1:28-Val-CAC-2 expression in NPC cells. Transfection was used to manipulate tRF-1:28-Val-CAC-2 expression levels, and proliferation, migration, and invasion were then evaluated through CCK-8, wound-healing, colony formation, and Transwell approaches. Apoptotic induction and cell cycle progression were assessed through flow cytometry, while EMT-related marker expression was assessed via qPCR and Western immunoblotting. The effects of tRF-1:28-Val-CAC-2 on the growth and distant metastasis of tumors were then tested in vivo using nude mice.ResultsNPC cells exhibited tRF-1:28-Val-CAC-2 upregulation that was associated with significantly increased proliferative, migratory, and invasive activity together with the suppression of apoptotic death. In vivo experiments further confirmed the ability of tRF-1:28-Val-CAC-2 to promote tumor growth and distant metastasis. At a mechanistic level, these effects were related to the control of EPHB2 gene expression by tRF-1:28 Val-CAC-2, thereby shaping the survival and malignancy of the cells.DiscussionThese results demonstrate that tRF-1:28-Val-CAC-2 promoted EPHB2 to enhance tumorigenic behavior in NPC cells, underscoring its key role as a novel target for therapeutic intervention.